LEMBAR KERJA PESERTA DIDIK BERBASIS DISCOVERY LEARNING PADA MATERI TRIGONOMETRI KELAS X SMA - Agnesa Hanravia (Departemen Matematika, 2021)
Based on the results of interviews with educators and students resulted in a conclusion that trigonometry material is a material that is difficult for students to understand because students tend to memorize formulas and are not actively involved in learning. Discovery learning is a learning model designed to develop students' active learning through the process of discovery and investigation independently, the application of learning with the discovery learning model also requires teaching materials as learning resources that support the learning process using the model, one of which is teaching materials that can be used are Student Worksheets (LKPD). This research is categorized as research and development with the help of the Plomp model. At the initial investigation stage (preliminary research) needs analysis, curriculum analysis, concept analysis, and student analysis are carried out. At the prototype stage (prototyping stage), the LKPD that has been designed is self-evaluated, followed by an expert review by three validators, then tested by one-to-one evaluation and testing. try a small group (small group) to class X high school students. This research produces LKPD based on Discovery Learning on trigonometry material with valid and practical criteriaKeywords -Development, Discovery Learning, Student Worksheet, and Trigonometry